(untitled) (Research, Society and Development, 2020)
In northeast Brazil, the most part of vegetation is a deciduous seasonally dry tropical forest called of “Caatinga”. Despite the semi-arid areas correspond to most of the caatinga vegetation, there are some areas 500 m above sea level with an annual rainfall up to 1200 mm forming evergreen forest enclaves. Macroarthropod abundance and fauna composition differences in Caatinga are related to seasonal rainfall effects but, this difference is unclear in the enclaves of evergreen forests. Thus, the aim of this study was to measure the effects of rainfall on insect, arachnid, and centipede assemblages in an enclave of evergreen forest within the Caatinga vegetation. We tested the following hypotheses: 1) rainfall changes arthropod abundance and species richness; 2) predator abundance correlate with prey, and 3) abundance arthropod abundance and species richness exhibit a delayed or anticipated response to rainfall. No effects of rainfall on insects and arachnids abudance were observed. There was a significant correlation between prey and predator abundance with changes in dominant species between the rainy and dry seasons. The insects and arachnids can show some anticipated responses to rainfall. The abundance and richness of centipedes were influenced by rainfall whith a delayed response. Our findings indicate that, in evergreen forest enclaves within Caatinga vegetation, the soil arthropods show different responses compared to rainfall than the most common areas of the Caatinga domain and an increase in the detection of insects and arachnids just before the beginning of the rainy season.